2014
DOI: 10.1007/s11103-014-0207-8
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional response of apple alcohol acyltransferase (MdAAT2) to salicylic acid and ethylene is mediated through two apple MYB TFs in transgenic tobacco

Abstract: Volatile esters are major factors affecting the aroma of apple fruits, and alcohol acyltransferases (AATs) are key enzymes involved in the last steps of ester biosynthesis. The expression of apple AAT (MdAAT2) is known to be induced by salicylic acid (SA) or ethylene in apple fruits, although the mechanism of its transcriptional regulation remains elusive. In this study, we reveal that two apple transcription factors (TFs), MdMYB1 and MdMYB6, are involved in MdAAT2 promoter response to SA and ethylene in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…This result is consistent with that by research reports on grape and Phyllostachys edulis [66,67], indicating that the promoter regulatory element of the MADS-box gene has a certain conservatism among different species. Previous studies have found that ABRE is associated with drought, ABA induction, and high salt stress in plants [68,69]. There were many ABRE elements in PgMADS13, PgMADS03, PgMADS16, PgMADS30, and PgMADS25, which were speculated to be related to pomegranate response to drought, ABA induction or high salt stress.…”
Section: Discussionmentioning
confidence: 87%
“…This result is consistent with that by research reports on grape and Phyllostachys edulis [66,67], indicating that the promoter regulatory element of the MADS-box gene has a certain conservatism among different species. Previous studies have found that ABRE is associated with drought, ABA induction, and high salt stress in plants [68,69]. There were many ABRE elements in PgMADS13, PgMADS03, PgMADS16, PgMADS30, and PgMADS25, which were speculated to be related to pomegranate response to drought, ABA induction or high salt stress.…”
Section: Discussionmentioning
confidence: 87%
“…However, (i) the relatively high expression of PpAAT1 in fruit, (ii) the in vitro enzyme activity and in planta overexpression results, and (iii) the correlation with ester contents across different cultivars all indicate that peach PpAAT1 is a major component of peach fruit volatile ester biosynthesis. Recently, TFs that regulate AAT expression have been identified in plants (Guo et al, 2018;Li et al, 2014). However, direct effects of these TFs on volatile ester synthesis remain undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that the promoter of the TALE gene has a certain conservative. Previous studies have found that ABRE is associated with plant drought, ABA induction, and high salt stress in plants [31,65]. In addition, there are a series of elements related to stress, such as ARE, MBS and LTR.…”
Section: Discussionmentioning
confidence: 99%
“…The dimer formed by the A. thaliana homeobox 1 (ATH1) protein and the shoot meristemless (STM) protein participates in the development of plant meristems [29], while the dimer formed by the ATH1 protein and the KNOTTED-like from A. thaliana 2 (KNAT2) protein regulates the development of plant inflorescence tissue [30]. The interaction of BLH6 and KNAT7 affects the development of secondary cell walls [31]. The KNOX gene family contains KNOX1, KNOX2, ELK and homeodomain, except for a novel gene KNATM without the homeodomain [32,33].…”
Section: Introductionmentioning
confidence: 99%